The estimation of the thermal efficency of panel type radiators by cfd analysis and an alternative desing research to increase efficiency - Aydar,Emir (My University, 2009)
PANEL TİP RADYATÖRLERİN ISIL VERİMLERİNİN CFD ANALİZİ İLE BULUNMASI VE VERİM ARTIŞI İÇİN YENİ DİZAYNLARIN ARAŞTIRILMASI Bu tez kapsamında mevcut panel radyatörün hesaplamalı akışkanlar dinamiği analizi bir ticari kod olan sonlu hacim metodunu kullanan STAR-CCM+ ile yapılacaktır. Nümerik termal performans değerleri elde edilecek ve katalogtaki değerler ile karşılaştırılacaktır. Bundan sonra, termal verimi arttırmak için yapılacak yapısal değişiklik aynı CFD kodunu kullanarak yapılacaktır. Giriş su sıcaklığı 75 °C ve sabit su debisi için çapraz bağlantılı radyatörlerin termal performansları ortam ısı transfer katsayıları değişimine bağlı olarak incelenmiştir. Aynı yönlü çelik panel radyatör ayrıca incelenmiştir. Verimi arttırmak için dört kanat dizaynı yapılmıştır. Daha verimli kanat elde edilmek için konvektör uzunluğu üç farklı kanat uzunluğuna kısaltılmıştır. Üçgen kanat uzunluğu ayrıca üç farklı kanat uzunluğuna kısaltılmıştır. Her dik kanalda su debisinin düzgün dağıtılması için panel ve dik kanalda modifikasyonlar yapılmıştır. Ortam ısı transfer katsayısı 6.5 W/ m²K için 65 °C su çıkış sıcaklığı elde edilir. İki ana bağlantı metodu bu panel radyatör için kullanılabilir. Üçgen kanat dizaynı diğer yeni dizaynlara göre daha verimlidir. Panel radyatörün kanat uzunluğu kısaltılması ile daha verimli kanat elde edilir. Panel radyatörün panel genişliği arttırılarak ve dik kanal genişliği azaltılarak su debisi bütün dik kanallardan neredeyse eşit miktarda geçer. Panel Radyatör, Termal Performans, Hesaplamalı Akışkanlar Dinamiği, Sonlu Hacim Metodu.

THE ESTIMATION OF THE THERMAL EFFICIENCY OF PANEL TYPE RADIATORS BY CFD ANALYSIS AND AN ALTERNATIVE DESIGN RESEARCH TO INCREASE EFFICIENCY Within the scope of this thesis computational fluid dynamic analysis of existing panel radiators were made with a commercial CFD code of STAR-CCM+ using finite volume method. Numerical thermal performance values were obtained and compared given catalogue values. After that, structural change to increase the thermal efficiency will be done by using the same CFD code. For the fix inlet water temperature of 75 °C and fix mass flow inlet, thermal performance of the radiator with TBOE connection was examined depending on the alternation of ambient convective heat transfer coefficient. Steel panel radiator with TBSE connection was also investigated. In order to increase efficiency four convector designs were created. In order to obtain more efficient convector, the width of the convector was reduced to three different convector widths. The width of the triangle convector design was also reduced to three different convector widths. In order to distribute the mass flow rate at each vertical duct uniformly, modifications at panel and vertical duct were performed. Outlet water temperature of 65 °C was obtained for the ambient convective heat transfer coefficient of 6.5 W/ m²K. Two basic connection methods can be used for this panel radiator. Triangle convector design is more efficient than the other new designs. By shortening the convector width of the panel radiator, a more efficient convector is acquired By enhancing the panel width of the panel radiator and reducing the vertical duct width of the panel radiator, the mass flow rate passes through all vertical ducts almost in equal amounts. Panel Radiator, Thermal Performance, Computational Fluids Dynamic, Finite Volume Method.
Keywords: Makine_Alternatif Dizayn; Mühendislik; Mühendislik_Akışkanlar